2014
DOI: 10.1007/s10792-014-9920-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pupillary response to light in patients with glaucoma: a study using computerized pupillometry

Abstract: The aim of this study was to evaluate pupillary response to light stimulation in patients with different stages of glaucoma using computerized pupillometry. We conducted a retrospective study on a group of 44 glaucoma patients who had undergone complete ophthalmological examination, visual field test (Humphrey SITA Standard 24-2) and monocular dynamic pupillometry (MonCV3 Metrovision). Eyes were classified into stages of glaucoma according to visual field damage using the Glaucoma Staging System 2. A group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…They also suggested that the short chromatic pupillometry test may be useful to detect glaucoma . In another study, Martucci et al evaluated the pupillary light reflex in patients with different stages of open‐angle glaucoma by a computerised pupillometry and showed a significant correlation between pupil contraction speed, minimum pupil diameter, percent pupil contraction, initial pupil diameter values and the stage of glaucoma. All of these aforementioned studies confirmed that glaucoma is associated with altered pupillary responses.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggested that the short chromatic pupillometry test may be useful to detect glaucoma . In another study, Martucci et al evaluated the pupillary light reflex in patients with different stages of open‐angle glaucoma by a computerised pupillometry and showed a significant correlation between pupil contraction speed, minimum pupil diameter, percent pupil contraction, initial pupil diameter values and the stage of glaucoma. All of these aforementioned studies confirmed that glaucoma is associated with altered pupillary responses.…”
Section: Discussionmentioning
confidence: 99%
“…nervous system (CNS). It is now believed that neuronal degeneration in glaucoma is not limited to the eye but also extends, triggered by different molecular pathways, to the central visual areas, affecting the lateral geniculate nucleus, the visual cortex and the afferent pathway (Nucci et al, 2003Martucci et al, 2014). In particular, the atrophy of neurons in the lateral geniculate nucleus and the visual cortex has been documented in primates with experimental glaucoma (Yücel et al, 2000(Yücel et al, , 2003Weber et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This tool provides unique opportunities to examine the responses of one of the many types of RGCs against OHT-induced degeneration. m + RGCs constitute between 2% and 3% of all RGCs in adult rats (2.5% and 2.7% for albino and pigmented, respectively; Galindo-Romero et al, 2013a;Nadal-Nicolás et al, 2012 and mice (2.5% and 2.1% for albino and pigmented, respectively; Valiente-Soriano et al, 2014;Vugler et al, 2015), and recent evidence indicates glaucoma courses with a number of altered nonvisual-forming functions (Feigl et al, 2011;Kankipati et al, 2011;Martucci et al, 2014;Nissen et al, 2014;Pérez-Rico et al, 2010). Moreover, experimental glaucoma in rats has been shown to present important alterations of the circadian rhythms (de Zavalía et al, 2011;Drouyer et al, 2008;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%